Ground-based MAX-DOAS observations of tropospheric aerosols, NO2, SO2 and HCHO in Wuxi, China, from 2011 to 2014 - Wang, Yang; Lampel, Johannes; Xie, Pinhua (Atmospheric chemistry and physics, 2017)
Abstract. We characterize the temporal variation and vertical distribution of nitrogen dioxide (NO2), sulfur dioxide (SO2), formaldehyde (HCHO) and aerosol extinction based on long-term multi-axis differential optical absorption spectroscopy (MAX-DOAS) observations from May 2011 to November 2014 in Wuxi, China. A new inversion algorithm (PriAM) is implemented to retrieve profiles of the trace gases (TGs) and aerosol extinction (AE) from the UV spectra of scattered sunlight recorded by the MAX-DOAS instrument. We investigated two important aspects of the retrieval process. We found that the systematic seasonal variation of temperature and pressure (which is regularly observed in Wuxi) can lead to a systematic bias of the retrieved aerosol profiles (e.g. up to 20 class="thinspace" for the AOD) if it is not explicitly considered. In this study we take this effect into account for the first time. We also investigated in detail the reason for the differences of tropospheric vertical column densities derived from either the geometric approximation or by the integration of the retrieved profiles, which were reported by earlier studies. We found that these differences are almost entirely caused by the limitations of the geometric approximation (especially for high aerosol loads). The results retrieved from the MAX-DOAS observations are compared with independent techniques not only under cloud-free sky conditions, but also under various cloud scenarios. Under most cloudy conditions (except fog and optically thick clouds), the trace gas results still show good agreements. In contrast, for the aerosol results, only near-surface AE could be still well retrieved under cloudy situations. After applying a quality control procedure, the MAX-DOAS data are used to characterize the seasonal, diurnal and weekly variations of NO2, SO2, HCHO and aerosols. A regular seasonality of the three trace gases is found, but not for aerosols. Similar annual variations of the profiles of the trace gases appear in different years. Only NO2 shows a significant seasonality of the diurnal variations. Considerable amplitudes of weekly cycles occur for NO2 and SO2, but not for HCHO and aerosols. The TGs and aerosols show good correlations, especially for HCHO in winter. More pronounced wind direction dependencies, especially for the near-surface concentrations, are found for the trace gases than for the aerosols, which implies that the local emissions from nearby industrial areas (including traffic emissions) dominate the local pollution, while long-distance transport might also considerably contribute to the local aerosol levels.
Im Titel ist die Zahl 2 in der chemischen Formel tiefgestellt
Gesehen am 27.11.2018